Analyzing the Effect of Dancesport on Reducing Menopausal Symptoms and Increasing Quality of Life - Kumaat, Noortje Anita; Sulistyarto, Soni; Dewi, Ratna Candra; Wahyudi, Heri; Sulistyana, Caturia Sasti; Susanto, Nugroho; Eken, Ozgur; Purwoto, Septyaningrum Putri (Physical Education Theory and Methodology, 2025)
Background. The increasing popularity of dancesport is being observed worldwide, with Indonesia also embracing this trend. Nevertheless, there is still a lack of data to establish if dancesport can help with menopausal symptoms and enhance quality of life. Objectives. This study aimed to investigate the impact of a 12-week dancesport program on decreasing menopausal symptoms and improving quality of life. Materials and methods. A quasi-experimental design was used with a pretest-posttest method. The study included 30 women who had gone through menopause and were between the ages of 54 and 63. The WHOQOL-BREF questionnaire was used to evaluate the quality of life, and the Menopause Rating Scale (MRS) was employed to assess the severity of menopausal symptoms. The program involved a 12-week dance course, meeting twice a week for 60 minutes per session, including cha-cha, salsa, rumba, hip-hop, and waltz dances. Data analysis was conducted using SPSS 24, beginning with descriptive statistics, then progressing to normality testing using the Shapiro-Wilk test, and finally paired samples t-tests. Results. The findings indicated a noteworthy influence of the 12-week dancesport intervention on menopausal symptoms and quality of life, with a significance level of 0.000 (< 0.05). Conclusions. The study found that dancesport is beneficial for postmenopausal women by improving symptoms and quality of life, suggesting further research into the impact of these programs on men experiencing andropause-related changes.